2019
DOI: 10.1038/s41386-019-0537-y
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of peripheral nerve injury-induced neuropathic pain and cognitive dysfunction via genetic and tomivosertib targeting of MNK

Abstract: Neuropathic pain caused by nerve injury presents with severe spontaneous pain and a variety of comorbidities, including deficits in higher executive functions. None of these clinical problems are adequately treated with current analgesics. Targeting of the mitogen-activated protein kinase-interacting kinase (MNK1/2) and its phosphorylation target, the mRNA cap binding protein eIF4E, attenuates many types of nociceptive plasticity induced by inflammatory mediators and chemotherapeutic drugs but inhibiting this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 59 publications
1
51
0
Order By: Relevance
“…Activation of MNK-eIF4E signaling by type I IFNs has been observed in other cell types where it has been linked to increased immune surveillance (Joshi et al, 2009). Multiple previous studies have demonstrated that activation of MNK-eIF4E-mediated translation events are causative in the production of chronic pain states, including neuropathic pain (Moy et al, 2017; Megat et al, 2019; Shiers et al, 2019). Since both viral infections and prolonged production of type I IFNs can cause neuropathic pain, it is possible that type I IFN receptor signaling to MNK-eIF4E may be a key pathway for production of these types of neuropathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of MNK-eIF4E signaling by type I IFNs has been observed in other cell types where it has been linked to increased immune surveillance (Joshi et al, 2009). Multiple previous studies have demonstrated that activation of MNK-eIF4E-mediated translation events are causative in the production of chronic pain states, including neuropathic pain (Moy et al, 2017; Megat et al, 2019; Shiers et al, 2019). Since both viral infections and prolonged production of type I IFNs can cause neuropathic pain, it is possible that type I IFN receptor signaling to MNK-eIF4E may be a key pathway for production of these types of neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“…A key pathway linking initial nociceptor activation to nociceptor hypersensitivity and potentially the development of chronic pain is engagement of translation regulation signaling (Obara and Hunt, 2014; Khoutorsky and Price, 2018; de la Pena et al, 2019). Importantly, eIF2α phosphorylation, mTORC1 activation and MNK-eIF4E signaling can all lead to persistent sensitization of nociceptors and all of these pathways have been linked to neuropathic pain disorders (Inceoglu et al, 2015; Khoutorsky et al, 2016; Moy et al, 2017; Megat et al, 2019; Shiers et al, 2019)…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in spatial memory were also found in SNI mice on day 14 [37,75] and 30 [36] from surgery. Impairment in cognitive flexibility was also detected in mice in the attentional rule-shifting task 21 days after SNI surgery [76]. Curiously, no impairment in spatial working memory was found in the Morris water maze 3 to 21 days after SNI in mice by Karl et al [77].…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 97%
“…A target identified from that paper was the RNA binding protein, eIF4E, the phosphorylation of which has been implicated in coronavirus replication (Banerjee et al, 2002;Mizutani et al, 2004) and the suppression of anti-viral responses (Herdy et al, 2012). Previous work suggests that eIF4E phosphorylation by MNK, a druggable target identified by Gordon et al (2020), plays a key role in regulating the excitability of nociceptors (Moy et al, 2017;Megat et al, 2019;Shiers et al, 2020) and also regulates the translation of many cytokines and chemokines (Furic et al, 2010;Herdy et al, 2012;Amorim et al, 2018). Based on this, we intersected differentially expressed BALF ligand and receptor genes in COVID-19 samples with mRNAs known to be regulated by eIF4E phosphorylation from previous studies (Furic et al, 2010;Aguilar-Valles et al, 2018;Amorim et al, 2018).…”
Section: Possible Pharmacological Intervention Points For Existing Ormentioning
confidence: 99%